(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
BACKGROUND: Little is known about the health care spending distribution across the age and sex gradient in European systems. The aim of the present study is to examine gender and age differences in health care utilization in Lombardy, Italy. METHODS: We analysed administrative data for the year 2010 in Lombardy (the largest Italian region, with about 10 million inhabitant) including spending for inpatient and outpatient services and pharmaceuticals. Data were aggregated across age and sex. RESULTS: Lombardy in 2010 spent around 10.2 billion €, 51% of which for women. Age-standardized per-patient expenditure was however 5% lower for females than for males on average. Per-patient spending on elderly women (>65) was around 75% of the spending on men of the same age group. Further, health expenditure was higher for men for the treatment of chronic diseases. Importantly, the difference persisted after allowance of history chronic conditions. CONCLUSIONS: Our results are in sharp contrast with the US based literature showing that health expenditure in women is greater than in men. This may reflect inadequate attention to health care of women in Italy